Determination of shear wave velocity by using multichannel analysis of surface wave and borehole measurements: A case study in Ho Chi Minh City - Tran Duy Tap; Nguyen Nhat Kim Ngan; Do Van Luu; Nguyen Thanh Vanb (Lowland Technology International, 2020)
The soil characterization of the residential development project located in Ho Chi Minh City (HCMC) was conducted by using multichannel analysis of surface wave (MASW) and downhole measurements. The obtained results of both methods indicate that the soils within the depth range of 0-30 m were divided into three layers including (i) the filled soil with shear wave velocity (VS) values of 75-93 m/s, (ii) the silty clay with VS of 61-200 m/s, and (iii) the firm layer soil with VS of 250-415 m/s. The VS30 values estimated by using the MASW, downhole, and empirical correlation methods are in the range of 150-152, 137-161, 126-171 m/s, respectively. Accordingly, the study area is well classified as class E according to National Earthquake Hazards Reduction Program guidelines (NEHRP). The MASW results are in good agreement with those obtained by using the downhole measurements with the average relative difference of 3-4%. This study represents a first attempt of using the MASW method to evaluate the stiffness of soil around HCMC areas and the results obtained from this method and correlation between standard penetration test (SPT)-N and VS can contribute a further detailed understanding of geophysical features in the HCMC area.